Sorghum - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Sorghum by Hugh Doggett, is a new edition in the Longman Scientific and Technical series, 688 pages; price UK L 45.00 ISBN 0 582 46345 9